(untitled) (Research, Society and Development, 2020)
Introduction: Periodontitis is characterized by tissue changes such as gingival inflammation, destruction of the periodontal ligament and the alveolar bone. Metabolic syndrome (MS) is defined by a set of metabolic changes (dyslipidemia, arterial hypertension, glucose intolerance, central obesity and insulin resistance), which commonly manifest as comorbidities. Objective: To compare different criteria for diagnosing periodontitis, as well as the criteria for diagnosing MS and to identify differences between them according to sex. Method: Cross-sectional study conducted with 90 users of the Family Health Unit (USF) Vale do Cambonas in Salvador-Ba, developed with the application of a questionnaire, physical / anthropometric, dental, medical records and laboratory exam reports. Results: Good agreement was verified between the criteria for the diagnosis of MS (Kappa = 0.8230) and average agreement comparing three different periodontitis diagnostic criteria proposed. Men had worse periodontic conditions than women. These showed worse metabolic rates. As for the number of teeth, there was a trend towards an association between tooth loss and diabetes. Conclusion: The divergence observed between the diagnostic criteria of periodontitis corroborates the difficulty in standardizing this diagnosis, making it difficult to compare scientific findings and the differences found between genders related to the diagnosis of MS. Periodontal parameters and clinical and laboratory characteristics proved to be relevant, requiring further studies to deepen them.